Hubungan antara Dukungan Suami dengan Tingkat Stres Istri yang Menderita Kista Ovarium di Purwokerto - Triyanto, Endang (Jurusan Keperawatan FIKES UNSOED, 2009)
Disorders of the women ovary can lead to impaired growth and development as well as maturity of the ovum, so that it could make high risk for women to become fertile. The most disorder that commonly occurred in women is ovarian cysts. This situation become worst if her husband doesn’t support and tend to blame his wife. The purpose of this study is to describe related the role of husband to stress levels his wife who suffered from ovarian cysts. Sampling techniques performed in this study is purposive sampling. Respondents were ovarian cyst women who live in Purwokerto during April to June 2009. The results of this study show that from three type of husband role support, instrumental support has the highest score at (41%). In addition, emotional and informational support have score at (33%) and (26%) respectively. There is a relationship between a husband to support his wife who suffered from stress levels of ovarian cysts with p = 0.02 at 95% Confident Interval (CI). Husband should provide good support to his wife's health condition or illness.